Peran Switching Costs Sebagai Variabel Moderasi Pada Pengaruh Kepuasan Atas Kualitas Jasa Terhadap Loyalitas Nasabah Pt. Bank Negara Indonesia (Persero) Tbk. Cabang UNAIR Di Surabaya - Indrianawati Usman; Ricky Gandhi Saputra (Universitas Airlangga, 2009)
This paper examine the influence of satisfaction at service quality (SERVQUAL) that related to customer loyalty with moderated by switching costs in PT. Bank Negara Indonesia (Persero) Tbk branch UNAIR Surabaya. Variable conduct in this paper is satisfaction at service quality (X), switching costs (Z), and loyalty (Y). Sampling is conducted by purposive non random sampling and use moderated regression analysis to analyze data. The result indicates effect of customer satisfaction on loyalty in customers is less when switching cost is perceived to be high rather than low. In other words, perceived switching cost reduces customers’ sensitivity to the level of customer satisfaction.